PENENTUAN KRITERIA DALAM PEMILIHAN JENIS PERKERASAN PADA DATARAN TINGGI DI KABUPATEN TRENGGALEK - Anang Prayogo; Hitapriya Suprayitno; Herry Budianto (Institut Teknologi Sepuluh Nopember (ITS), 2018)
Road infrastructure at hilly area is highly needed and very important to support the economics stability in thedistrict of Trenggalek. Road infrastructure becoming the most important nowadays for the people of Trenggalek especially forthose who live in the highland. The problems recently happened until now is the road infrastructure in the district ofTrenggalek especially in the highland are many damaged, not feasible and many more that requires to be restored. The typeselection of the pavement that proper and suit for the highland in the district of Trenggalek is highly influenced by somecriteria. And from some literature study we can draw conclusions in 6 (six) criteria those are, road user safety, road useramenities, cost of construction, ease of execution for the road construction, treatment of the road construction after themaintenance period expired and the availability of the materials. Then from interviewing the respondents that hasexperienced in the road construction especially in the highland of Trenggalek concluded 7 (seven) criteria those are, roaduser safety, road user amenities, cost of construction, situation and condition of the project location, treatment of the roadconstruction after the maintenance period expired and the durability to the scouring water.